PELATIHAN HIGIENE SANITASI PANGAN SEBAGAI UPAYA MENINGKATKAN KESEHATAN MASYARAKAT DI KELURAHAN BUGEL, KECAMATAN PANJATAN, KULONPROGO, DIY - Anna Rakhmawati; Tien Aminatun; Bernadetta Octavia; Suhartini (Universitas Merdeka Madiun, 2026)
Cases of poisoning and disease due to consuming food still occur. The program target to increase the knowledge and skills of food business community in Kelurahan Bugel Kecamatan Panjatan, Kulonprogo, DIY in recognizing and identifying food sanitation hygiene as well as improving skills in identifying potential food hazards. Moreover, to assist and motivate food business community to implement the knowledge and skills in preventing food poisoning so as to improve public health. The activity methods carried out are preparation, implementation, evaluation, and improvement. The preparation stage includes hearings, coordination, and strengthening the program. The identifying participants, were 23 food business community. The implementation stage is seminar activities by providing materials, practical, and training. The material was delivered by the lecturer team, followed by skills training to characterize potential hazards. Both physical, chemical and biological hazard in food ingredients were identified and efforts to prevent contamination. The final activity was evaluation and improvement. The program results show the success of the process as demonstrated by participant attendance reaching 92%, increased knowledge and skills in identifing potensial hazard, also choosing safe food ingredients. The results of the participant satisfaction questionnaire showed that participant satisfaction in all aspects was good and very good.